Maisir Chip Higgs Domino Transactions on Online on the Millenial Generation in Bengkalis Regency, Riau Indonesia - Zulfikar Hasan; Oliv Rezfani; Ahmad Syukri (Universitas Darussalam Gontor, 2023)
The online Higgs domino maisir chip transaction among millennials in the Bengkalisregion is the focus of this study. The purpose of this study was to determine how the millennial generation views online Higgs domino chip transactions and how they affect them. This kind of exploration is subjective examination. This kind of research uses descriptions and field conditions to develop concepts, understandings, and theories. Descriptive analysis is the method used in this study, which aims to accurately describe a person, disease, symptom, or group. The Interview is the method that is used to collect data. It is a form of verbal communication that aims to gather information. Written documents like diaries, magazines, documents, meeting minutes, and others are used to gather information on Islamic law and opinions about the Maisir Higgs domino chip transaction in the Bengkalis area for the millennial generation. The law of online Higgs domino maisir chip transactions, which includes the prohibitions of gharar, usury, and maisir from an Islamic economic perspective, are the findings of this study.